Omni-channel retail strategies and customer loyalty: A focus on E-commerce stores in Nigeria - Chiyem, Iyadi Rollins; Ofili, Peter Nkeonyeasua; Nelson, Edeme Chidi; Ebele, Eboh Mercy (Edelweiss Applied Science and Technology, 2024)
The growth of Omni-channel retailing is causing consumers to change their habits and shopping behaviour. It is essential to understand the factors on customer loyalty within the consumer context. The purpose of this paper is to explore factors that are influencing consumer’s loyalty when they use omni-channel in their shopping behaviour, specifically in the E-commerce sector in Nigeria. There have been significant developments in the field of retailing with digitalization. One of these developments is the emergence of Omni-channel retailing. Although this has affected both firms and consumers considerably, the literature is dominated by the studies dealing with omni-channel retail strategy and customer loyalty. The purpose of this paper is to empirically investigate the relationship between Omni-channel retail strategy and customer loyalty. Three research objectives were identified and translated into three research questions which were aptly answered by subjecting them to a test of hypotheses. A descriptive survey research method was used to survey selected E-commerce stores (jumia, konga and Jiji) outlets in Delta state, Nigeria. However, the findings of the study revealed that the constructs of Omni-channel retail strategy; online and in-store integration, offering in-store pick up and Mobile apps have significant effect on Customer loyalty. Thus, it was concluded that Omni-channel retail strategy represents the evolution of technology and the full integration of business resources. It empowers customers by giving them the freedom of choice to move across different channels without barriers, directing marketing activities to be customer-centred and designed according to customer’s needs. The study recommended that E-commerce stores in Nigeria should develop customized Omni-channel strategies that align with local consumer preferences and market dynamics. This entails leveraging online and offline channels synergistically to deliver seamless shopping experiences.